Caring for children and youth from Canada's military families. Issue 2 (13th September 2021) - Cramm, Heidi; Mahar, Alyson; Tam-Seto, Linna; Rowan-Legg, Anne
Abstract: Introduction: The lives of Canada's military families are characterized by persistent stressors that can play a role in the health and development of children and youth. Military families are cared for by civilian physicians who may not be aware of this unique experience and risk. Our study sought to explore the knowledge and experiences of paediatricians providing care to Canadian Armed Forces (CAF) families. Methods: A 14-item survey was disseminated electronically by the Canadian Paediatric Surveillance Program (CPSP) to all 2799 Canadian paediatricians and paediatric specialists registered with the CPSP. Questions were focused on: knowledge of CAF families; the impact of the military on family care; confidence in providing care to CAF families; and training/education needs. Results: A total of 774 (28%) completed surveys were received. Approximately one third of respondents incorrectly believed that CAF families receive services from the federal military healthcare system. Nearly one quarter did not feel that identifying for military status informed patient care. Over half of respondents do not feel adequately prepared to provide care to CAF families. Discussion: Findings from this exploratory study suggest that additional resources and training would benefit the care of CAF families. Conclusion: CAF families experience a collection of risk factors that may negatively affect their health and access to services. The survey findings provide evidence of a need to further military literacy amongst Canadian paediatricians and provide direction for the development of enhanced resources and supports.